1996
DOI: 10.1107/s0108768196004673
|View full text |Cite
|
Sign up to set email alerts
|

Static disorder in the incommensurate structure of the high T c superconductor Bi2Sr2CaCu2O8+δ

Abstract: The incommensurate modulated structure of the high Tc superconductor of nominal composition Bi2Sr2CaCu2O8 has been refined using an optimized data set of 1530 reflections (496 main reflections, 753 first-order and 281 second-order satellites) in superspace group Bbmb(Oβ1) using a Fourier expansion of the modulation functions up to second order. A large improvement of the R (wR) factor [global: 0.056 (0.051); main reflections: 0.049 (0.043); first-order satellites: 0.056 (0.058); second-order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 6 publications
3
33
0
Order By: Relevance
“…There may be a number of sources for this non-uniformity, such as defects and thermal fluctuations, which may be enhanced by inhomogeneous heating effects [22]. Here it is assumed that the primary source of the inhomogeneities is thermodynamic fluctuations, but the model can also be employed to approximate smooth stoichiometry variations [29,30]. In the samples used in the experiments [26], the BSCCO crystals were prepared slowly over a very limited central region in gold-plated elliptical heating ovens, with highly controlled heating, producing samples that are probably much more uniform chemically (although still highly non-stoichiometric) than in those studies [31,32].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…There may be a number of sources for this non-uniformity, such as defects and thermal fluctuations, which may be enhanced by inhomogeneous heating effects [22]. Here it is assumed that the primary source of the inhomogeneities is thermodynamic fluctuations, but the model can also be employed to approximate smooth stoichiometry variations [29,30]. In the samples used in the experiments [26], the BSCCO crystals were prepared slowly over a very limited central region in gold-plated elliptical heating ovens, with highly controlled heating, producing samples that are probably much more uniform chemically (although still highly non-stoichiometric) than in those studies [31,32].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Note also that each [CoO 2 ] layer is inserted between two RSS, whose D zones are shifted by $7/4a 11 . Otherwise, in contrast with the Bi 2201 and 2212 modulated compounds with Cu, Fe and Co (see, for example, Leligny et al, 1992;Yamamoto et al, 1992;Tarascon et al, 1989;Jakubowicz et al, 1999;Grebille et al, 1996;Petr Ïõ Âc Ïek et al, 1990;Le Page et al, 1989;Pe  rez et al, 1997), no signi®cant puckering of the [BiO] and [SrO] layers along a 13 is observed in the composite crystal. This particular characteristic most probably originates from the fact that the Co atoms are only bound to the O3 atoms of the [CoO 2 ] layers, which appear as rigid structural units.…”
Section: The Intrinsic Modulationmentioning
confidence: 99%
“…Fortunately, however, significant variations in cell dimensions and geometry occur naturally at the nanoscale in the Bi 2 Sr 2 Ca nϪ1 Cu n O 4ϩ2n (n ϭ 1, 2, 3) family. These variations take the form of a bulk incommensurate periodic modulation (12)(13)(14)(15)(16)(17) perturbing the atoms from their mean positions (18), as shown schematically in Fig. 1 C and D. This so-called crystal ''supermodulation'' is believed to originate from a misfit between the preferred bond lengths of the perovskite and rock-salt layers of the crystal.…”
mentioning
confidence: 99%